Analisis Bibliometrik terhadap Bahan Ajar Matematika Berbasis Vosviewer - Radhiatul Asna (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
When children learn math, there are various misconceptions and lack of understanding of the ideas. It will be difficult for students to answer math problems if they do not understand the principles they learn in math class. The purpose of this study was to determine the current state of the research field of mathematics teaching materials and to identify potential future research topics. This research methodology uses bibliometric analysis. The research data was obtained through the Publish or Perish software with the Google scholar database, the keywords of mathematics teaching materials and the maximum number of results "1000", the articles obtained were 760 articles with a period of 2013-2023 The results showed that the trend of publications with the theme of mathematics teaching materials research experienced the highest increase between 2014-2017.